Designing a Microinsurance Program for Trade Union Members in Cambodia - Almazan, Rainier V.; Suan, Ivy D. C.; Rey, Mia P. (Philippine Management Review; Vol 14 (2007), 2011)
Over two decades of war have left Cambodia as one of the poorest countries in the world today. Social protection and insurance are currently in the incipient stage and there is no organization, public or otherwise, that addresses the risks and vulnerabilities of the workers and of the poor. This study was undertaken primarily to establish the feasibility of providing social protection coverage for organized formal and informal workers in Cambodia. It aims to design a microinsurance product and benefit package that may be initially offered to interested members of trade unions. This is also in response to a growing need for trade unions to provide innovative strategies that will alleviate the effects of poverty and consequently, improve its members' welfare and economic well-being. Survey results, focus group discussions, and interviews with key informants were the instruments used to define the characteristics of the target market so as to be able to create a product suited to their needs and financial capabilities.